Using Text Sets to Engage Students while Reading Canonical Literature in a Language Arts Classroom (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
Presenting canonical literature in the classroom can result in little engagement with students. However, these texts can still be useful in classrooms today because of the themes often presented. For example the topics of greed, jealousy, love, death, and betrayal are still relevant today. Students are often bored or uninterested in canonical literature for three main reasons; they are unable to make connections with the material, the language can be difficult for students to understand, and because the same text are often used students don’t see reading the texts as necessary. Text sets provide one solution to this issue by presenting students with multiple texts all centered around one theme or essential question which will be the focus of the unit. A text set includes both canonical literature as well as modern texts which are presented to the students in different medium to increase student engagement.
Keywords: Text Sets; Canonical Literature